2014
DOI: 10.1007/s13197-014-1364-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a comprehensive model for map of fruits based on enzyme kinetics theory and arrhenius relation

Abstract: MAP is a dynamic system where respiration of the packaged product and gas permeation through the packaging film takes place simultaneously. The desired level of O 2 and CO 2 in a package is achieved by matching film permeation rates for O 2 and CO 2 with respiration rate of the packaged product. A mathematical model for MAP of fresh fruits applying enzyme kinetics based respiration equation coupled with the Arrhenious type model was developed. The model was solved numerically using MATLAB programme. The model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 30 publications
(33 reference statements)
0
39
0
Order By: Relevance
“…In addition, the linear correlations (R) relevant to the linear fittings under different thermolysis conditions were all greater than 0.98, suggesting a good linear dependence between ln(g(α)/T 2 ) and 1/T. This result further indicated that the pyrolytic process of CC fractions can be explained in terms of the first-order-reaction with the Arrhenius theory (Masgrau et al 2003;Mangaraj et al 2015).…”
Section: Influence Of Different Process Parameters On Thermal Dynamicmentioning
confidence: 69%
“…In addition, the linear correlations (R) relevant to the linear fittings under different thermolysis conditions were all greater than 0.98, suggesting a good linear dependence between ln(g(α)/T 2 ) and 1/T. This result further indicated that the pyrolytic process of CC fractions can be explained in terms of the first-order-reaction with the Arrhenius theory (Masgrau et al 2003;Mangaraj et al 2015).…”
Section: Influence Of Different Process Parameters On Thermal Dynamicmentioning
confidence: 69%
“…In a MAP system, there is a change in the concentration of gases in the packaging headspace due to the dynamic interaction between the metabolic and biochemical processes of the packaged product on the one hand, in which O 2 is consumed and CO 2 , ethylene and water vapor are generated, and on the other hand, the transfer of all of these gases through the packaging. Accordingly, O 2 from the external atmosphere will be entering through the packaging to replace that the product is consuming and the other gases will be leaving out through the packaging system as surplus [11,[13][14][15]. The aim of the system is to balance these two processes in such a way that constant levels of these different gases are reached in the packaging headspace and that these equilibrium levels are as favorable as possible to preserve the product [9].…”
Section: Modified Atmosphere Packagingmentioning
confidence: 99%
“…This is of limited utility if it is not considered that regardless of the initial concentration of gases in the packaging headspace, the final concentration of these will depend on the interaction between the metabolic processes of the product (and possible microorganisms present) and the exchange of gases through the packaging. Failure to know the different rates at which these processes are carried out will result in an inadequate MAP, resulting in concentrations of gases that do not contribute to preserving the product at the best or that directly increase its deterioration at the worst [9,14]. For this reason and in order to obtain a satisfactory MAP, it is necessary to design the packaging system previously, and this basically consists of determining the gas transfer capacity in the packaging that is required to balance the metabolic processes of the product to be packed and in this way, to achieve favorable gas concentrations for its preservation [13].…”
Section: Modified Atmosphere Packagingmentioning
confidence: 99%
See 2 more Smart Citations